Worrisome prevalence of waterpipe smoking among athletes - Nakhostin-Roohi, B.; Valizadeh, S. (Medicina dello Sport, 2011)
Aim. The aim of this study was to evaluate the prevalence of waterpipe smoking in athletes of Ardabil, a city in the Northwest of Iran.